Unique aspects of Islamic microfinance financing process: experience of Baitul Maal Wa Tamwil in Indonesia - Wulandari, Permata; Kassim, Salina; Sulung, Liyu Adikasari; , Niken Iwani Surya Putri (Emerald Group Publishing Limited, 2016)
The main challenge to the Islamic microfinance institutions such as BMT is to create a microfinance which is engaging the poor people’s characteristics since the people at the bottom of pyramid have unique socio-economic characteristics to be considered. Several researches have explored Islamic microfinance but, to the best of our knowledge, none have focused on Islamic microfinance peculiarities model in several region with different poor people characteristics. This literature gap motivates this study.